(untitled) (Proceedings of Southern Federal University. Philology, 2021)
DOI 10.18522/1995-0640-2021-1-58-67 The article defines and describes the main ways of suggestive impact in advertising texts. The language-specific nature of advertising texts is often reduced, as the marketing aspect is highlighted. One of the main functions of the advertising text is the suggestive function, since this type of texts is designed to impact a person emotionally, psychologically, and manipulatively. Despite a number of works devoted to linguistic suggestion in advertising, this aspect remains poorly studied, due to the constant expansion of the range of manipulative strategies used in advertising texts. The empirical material for the present study, i.e. advertising texts, was collected from English versions of ELLE, OUT, WOMEN’S HEALTH magazines. An advertising text is a complex semiotic unity with the following properties: polysemioticity (elements of various sign systems are used to construct such a text), imperativeness (an advertising text is designed to induce an addressee to act), and suggestiveness (texts of this type are saturated with persuasion techniques). Verbal and non-verbal levels of manipulative techniques are distinguished. They are background and color as main medium of conceptual information, re-accentuation, graphic techniques, words and phrases with positive semantics, imperative, lexical-stylistic and grammar-stylistic devices. Keywords: advertising text, suggestive function, suggestive impact, manipulative techniques.